Pedestal Study for Diversity of Fishes, Crabs and Shrimps in Kokkilai Lagoon of Sri Lanka - Krishanthan, G.; Thiruchchelvan, N.; Mikunthan, G. (Advances in Biological Research, 2015)
Kokkilai Lagoon is a large estuarine lagoon located in Mullaitivu and Trincomalee districts of Sri Lanka. It consists of sea grass beds, oyster beds, mangrove swamp and mudflats, particularly in the western and southern shores and bounded by cultivated lands and scrub forest and some by open forest patches. The natural productivity and rich diverse resources of gives economic values to the lagoon. Even though still there is no confirmation about its faunal and floral diversity. Since, a study was conducted during a year period of September 2012 to October 2013, with an objective of identification of fishes, crabs and shrimp found in the lagoon ecosystem. Study revealed that 55 fish species belongs to 34 fish families were recorded. Among fish families three families; Cichlidae, Clupeidae and Leiognathidae were observed as dominant diversity families in this lagoon. Most massive crab species Scylla serrata and prevails throughout the year. Portunus pelagicus also plentiful in lagoon mouth area. Penaeus monodon and Penaeus sp. also abundant in the lagoon with some peak seasons. However, lagoon is being subjected to significant anthropogenic pressures that threaten to diminish the value of its biodiversity, fisheries and natural habitats
Keywords: Fish; Prawn; Crab; Kokkilai; Biodiversity